Financial Distress, Audit Quality, and Earnings Management–Indonesia's Mining Sector Evidence - Dwi Haryono Wiratno; Krismiaji Krismiaji; Handayani Handayani; Sumayyah Sumayyah (Jurnal Maksipreneur, 2023)
This paper describes research that investigated the association between financial distress (Dist) and accrual earnings management (AEM), and the role played by audit quality (AQ) in that association. Financial distress is measured by The Modified Altman Z-Score for emerging markets (EMZ score), earnings management is measured by discretionary accrual, and audit quality is measured by audit-firm size (Big4). Data analysis was performed with Pooled Least Square. Using data from Indonesian Mining Sector for 2016–2020, the research finds empirical evidence that financial distress firms involve in income-increasing accrual earning management, but such involvement is lower when firms are audited by Big 4 audit firms. This research contributes to previous literature about similar issues, specifically about the impact of financial distress on accrual earnings management. It also presents evidence about the role of audit quality in such an effect.